Sequence-based prediction of linear autoepitopes involved in pathogenesis of IPAH and the corresponding organism sources of molecular mimicry - Kubrycht, Jaroslav; Novotná, Jana (International journal of bioinformatics research and applications, 2014)
We proposed here a sequence-based approach predicting some microorganisms as possible sources of autoantigen-related molecular mimicry concerning Idiopathic Pulmonary Arterial Hypertension (IPAH) and related hypertension mostly accompanying autoimmune diseases and AIDS (APAH). This approach (SPECIES_VALENCE) processes the database occurrences of linear autoepitope-related short Dense Quasi-Pattern Sequences (DQPA) generated based on identities of important autoantigenic sequences. The corresponding enumeration comprises two types of statistical evaluations performed in each of eight proposed models. Based on this enumeration, we selected nine microorganisms, whereas revaluation of the obtained scoring values restricted Pseudomonas aeruginosa, Aspergillus fumigatus and the two co-infecting herpes viruses (Epstein Barr virus and cytomegalovirus) as most favourable. The results are discussed in terms of (a) the validity of increased DQPA occurrence in functionally correlated sequences, (b) the possible mechanisms leading to autoantibody response, (c) selected additional pathogenic effects of predicted microorganisms and (d) possible effects of cross-reactivities and immune tolerance.
Keywords: Molecular Sequence Data; idiopathic pulmonary arterial hypertension; autoantigens; sekvence aminokyselin; Molecular Mimicry; dense quasi–pattern sequences; APAH; fibrillin; DQPA; IPAH pathogenesis; sequence based prediction; bioinformatics; remodelling; organism sources; AIDS; molecular mimicry; konzervovaná sekvence; metalloproteinase; proline; zvířata; Humans; Amino Acid Sequence; autoantibody response; immune tolerance; molekulární mimikry; familiární plicní arteriální hypertenze; Species Specificity; autoimmune diseases; cross–reactivities; Familial Primary Pulmonary Hypertension; linear autoepitopes; druhová specificita; molekulární sekvence - údaje; Sequence Analysis, Protein; microorganisms; pathogenic effects; sekvenční analýza proteinů; Conserved Sequence; Epitopes; lidé; epitopy; Animals